Students’ Views on Utilizing Tiktok Daily Vlogs to Enhance Speaking Skills in English Learning - Cici Fahiroh Mufidatul Maulidiyah; Zainuddin Zainuddin; Beny Hamdani (Journey: Journal of English Language and Pedagogy, 2025)
The purpose of this study was to investigate how students felt about using TikTok daily vlogs as a language-learning resource perspectives on the aplication of tik tok daily vlog for education speaking English. This research used a quantitative methods involving 5 English study program students from UNZAH Universities. This study investigates how students use TikTok daily vlogs as a resource for improving their English speaking abilities. The objective of the examine is to understand the comprehensive effects, difficulties, and efficacy of using TikTok into language learning. English study program students were interviewed and given questionnaires as part of a qualitative descriptive approach. The results show that students view TikTok daily vlogs as an entertaining and useful way to get better at speaking, especially when it comes to confidence, fluency, and pronunciation. The study also emphasises how TikTok's engaging and interactive features encourage motivation and lessen nervousness when practicing speaking.However, students also mention a number of difficulties, including platform distractions and technological problems. The results of the study indicate that, when used with clear guidelines and objectives in mind, TikTok daily vlogs can be a helpful supplement to English language acquisition.